Enhanced ferroelectric polarization and magnetization in BiFe1−xScxO3 ceramics. (October 2015) - Wang, C.A.; Pang, H.Z.; Zhang, A.H.; Lu, X.B.; Gao, X.S.; Zeng, M.; Liu, J.-M.
Graphical abstract: Highlights: Single phase Sc doped BFO ceramics were successfully fabricated. Dielectric constant and magnetization are enhanced in doped BFO system. Polarization first increases and then decreases in doped BFO system. M r of 0.0105 emu/g and P r of 16.1 μC/cm 2 were revealed simultaneously at x = 0.01. Abstract: Multiferroic BiFe1− x Sc x O3 ceramics with x = 0.00–0.10 were synthesized by rapid liquid phase sintering. The influences of Sc doping on the crystalline structures, dielectric, ferroelectric, and magnetic behaviors of BiFeO3 ceramics were explored. The X-ray diffraction and the Raman spectrometric analysis revealed that all the samples are nearly single phase of rhombohedral structure with the incorporation of Sc ions into BiFeO3 . With increase doping concentration of x, the dielectric constant, dielectric loss, and remnant polarization for the doped BiFeO3 increase first and then drop down with further rise of x . A saturated ferroelectric polarization can be achieved at a small amount of Sc doping concentration ( x < 0.03), with a optimized remnant polarization of 17.6 μC/cm 2 at x = 0.03. Meanwhile, the magnetization is also slightly increased by introducing Sc dopant, with a maximum remnant magnetization of 0.0105 emu/g at x = 0.01. These results indicate that BiFeO3 ceramics with small amounts of Sc-doping may be promising for applications in magnetoelectric devices.